Safety and Efficacy of Insulin and Heparin in the Management of Hypertriglyceridemia-Induced Pancreatitis in a Patient without Diabetes: A Case Report - Luis Tolento Cortes; Jessica Trinh; Mimi Le; Philip Papayanis; Leah Tudtud-Hans; Lisa Hong (Case Reports in Endocrinology)
Acute pancreatitis (AP) leads to a variety of complications, such as local or systemic inflammatory responses as well as organ failure. While choledocholithiasis and alcohol abuse are two of the most common causes of AP, hypertriglyceridemia causes AP with an incidence rate between 2 and 5%. The management of hypertriglyceridemia-induced pancreatitis (HTGIP) is focused on the lowering of triglyceride (TG) levels, and the efficacy of therapies for the management of HTGIP may vary based on the hypertriglyceridemia etiology. The aim of this article is to report a case of a 43-year-old female with a history of familial hypertriglyceridemia and without diabetes who was admitted for acute pancreatitis with a TG level elevated to 4,435 mg/dL. The patient was treated with a combination of insulin, heparin, atorvastatin, and omega-3-acid ethyl esters, and her TG level was reduced to 880 mg/dL after 9 days of therapy. Despite the successful treatment of the patient, standardization of the approach for the treatment of HTGIP is needed. Future research should aim to identify the appropriateness of insulin therapy specifically in patients without diabetes presenting with hypertriglyceridemia and the dosing associated with optimal safety.